The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1994
DOI: 10.1002/tcm.1770140303
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxic effects of thalidomide derivatives in the non‐human primate Callithrix jacchus. IV. Teratogenicity of μg/kg doses of the EM12 enantiomers

Abstract: The dose-response of the teratogenic potency of the thalidomide (Thd) derivative EM12 was evaluated in the common marmoset (Callithrix jacchus). The smallest daily dose found to be effective was 30 micrograms EM12/kg body wt. This is the lowest dose of a Thd derivative ever reported to induce severe skeletal abnormalities. Ten micrograms EM12/kg body wt may be considered the no-observed-adverse-effect-level (NOAEL) under the experimental conditions chosen. The teratogenic potencies of the two EM12 enantiomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…We were also interested to determine whether the thalidomide enantiomers (R and S) and those of its more potent analog EM12 differ in their effects on explanted limb buds as they do in monkey embryos (Merker et al, 1988;Heger et al, 1994;Schmahl et al, 1996). Our data show that whereas R-thalidomide and R-EM12 do cause some limb defects, the S version of each is considerably more potent (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…We were also interested to determine whether the thalidomide enantiomers (R and S) and those of its more potent analog EM12 differ in their effects on explanted limb buds as they do in monkey embryos (Merker et al, 1988;Heger et al, 1994;Schmahl et al, 1996). Our data show that whereas R-thalidomide and R-EM12 do cause some limb defects, the S version of each is considerably more potent (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Muller and co-workers in attempts to improve the TNF-α inhibitory activity of thalidomide, described the structureactivity relationships of amino substitution of the phthaloyl ring of thalidomide (1) and isoindolinone ring of EM-12 (18), an analog that has been reported to be more potent teratogen than thalidomide in rabbits, rats and monkeys [71], on the TNF-α inhibitory activity in LPS stimulated human PBMC at concentration of 100 µM [72]. The results obtained indicated that introduction of amino group at the position 4 of phthalimide ring resulted in an improvement of TNF-α inhibitory activity (Fig.…”
Section: Synthetic Analogsmentioning
confidence: 98%
“…However, multigenerational studies are feasible in the marmoset, which has a comparatively short generation time (14-18 months) (Marshall et al, 2003b) To investigate the mechanism of thalidomide teratogenesis: metabolites of thalidomide may cause the down-regulation of surface adhesion receptors thereby altering cell to cell and cell to extracellular matrix interactions within the developing limb bud (Heger et al, 1988(Heger et al, , 1994Klug et al, 1994;Neubert et al, 1996) To examine the effect of luteinizing hormone and follicular stimulating hormone on granulosa cell development and steroidogenesis (Barrett, 2007;Millar et al, 2000;Hillier et al, 1997) To define the mechanisms of estradiol inactivation, in vitro fertilization, embryo transfer and parthenogenesis (Husen et al, 2001;Summers et al, 1987;Marshall et al, 1997Marshall et al, , 1998Marshall et al, , 2003aLuetjens and Wesselmann, 2008) To determine whether infant feeding with soya formula milk, which contains high levels of plant estrogens, poses any immediate or longer-term health risk to the developing testis and reproductive system of the male. An initial study found that testosterone levels were suppressed in animals fed with soya formula milk.…”
Section: Marmoset Use In Teratology and Reproductive Studiesmentioning
confidence: 99%